Protocolo de diagnóstico e tratamento da Neuropatia Diabética - VIEIRA, Jocyelle Nascimento (Universidade Federal do Pará, 2025)
Diabetic neuropathy (DN) is currently the most frequently observed chronic complication of diabetes mellitus (DM) and, at the same time, the most underdiagnosed, affecting up to half of these patients, depending on the diagnostic methodology used. It generally affects individuals with a long duration of the disease (>10 years), however, it may be present at diagnosis in patients with DM2 or manifest early, within the first five years of the disease, in patients with DM1. Additionally, once diagnosed, DN is usually irreversible, but its appropriate management in patients with early diagnosis increases the possibility of regression and stabilization of the disease, considerably delaying and preventing the onset of complications. The objective of this work was to create a protocol for diagnosing and treating diabetic neuropathy in an objective and didactic manner, with a focus on helping general practitioners and specialists, both in primary and tertiary care. The protocol was prepared using the integrative literature review method, which was divided into 6 phases. The first phase consisted of preparing the guiding question to define the studies to be included and then an integrative review was carried out in the PUBMED and SciElo databases with the terms “NEUROPATHY”, “TREATMENT”, “DIAGNOSIS”, “NEUROPATHY DIABETIC” and its counterparts in Portuguese. Guidelines from the main national and international diabetes scientific societies, one book and relevant information from relevant websites were also included. After data collection and analysis, 106 materials were used as theoretical references for the preparation of this protocol. This resulted in the construction of didactic and objective tables, charts and flowcharts. The clinical applicability of the study consists of providing a tool, not only for the specialist, but for the general practitioner at different levels of health care, with the aim of enabling effective care for individuals with DN. Thus, the main contributions of the protocol were the development of a total of 20 didactic and visual tools aimed at the prevention, tracking, diagnosis and treatment of DN. 5 flowcharts, 4 charts and 2 tables are authored by the author.